A higher order theory for bending of cross ply laminated cylindrical shell under hygrothermal loads - Syed Mohamed Ali, Jaffar; Alsubri, Saleh; Aminanda, Yulfian (Trans Tech Publications, Switzerland, 2015)
The combined effect of moisture and temperature on the bending behaviour of simply supported cross ply composite laminated shells has been investigated. A 13 term accurate higher order shear deformation theory with zigzag function is used in this analysis in which the effects of transverse shear deformation are taken into account. The results are presented for thermal load cases are validated against available 3D elasticity solutions in the literature and useful results for combined hygrothermal loading are presented in tabular and graphical form.